Pengembangan Tepung Labu Kuning, Tepung Ikan Gabus, dan Konsentrat Protein Kecambah Kedelai sebagai Bahan Penyusun Formula Enteral bagi Penderita Gagal Ginjal Kronik (Analisis Mutu Fisik, Kandungan Gizi, dan Kepadatan Energi) - Puti Mustika Swandyani; Agus Santoso; Yohanes Kristianto (Poltekkes Kemenkes Yogyakarta, 2016)
Background: Participation free radicals in biological processes have caused much damage in the human body including diseases chronic kidney failure (GGK). The number of sufferers of GGK is expected to continue to rise approximately 10 per year. One way to deal with it is to do a diet therapy through the granting of enteral formula for patients with GGK. Objective : The purpose of this study is to analyze the effect of snakehead fish, sprout soybean protein concentrate, and pumpkin flour to the physical quality, energy density, and nutritional content of enteral nutrition formulas for patients with Chronic Kidney Disease (CKD). Method:This type of research is experimental research laboratory with experimental designs “completely randomized design” using 4 levels treatment; P1, P2, P3, P4. Results: Enteral formula P4 has the best treatment than the other enteral formula products for CKD patients with 89.13 % water solubility; viscosity 136.66 cp; osmolarity of 387.17 mOsm/l; energy density 2.04 Kal/ml; carbohydrate content 57.29% of total energy; protein content 8.38% of the total energy; fat content 34.33% of energy total; water content 6.47%; ash content 1.96%; Quality protein/SAA 100%. Conclusion : Need a better packaging process so that the water content of CKD enteral formula can be stable. Keywords : Chronic Renal Failure, Enteral Formula, Snakehead fish flour, Sprouts Soybean Protein Concentrate, Pumpkin Flour